WOMEN ROLES IN WEDDINGS ETHNOGRAPHY OF WEDDING RITUALS AMONG RAJPUT IN PUNJAB PAKISTAN - Atifa Durrani; Rana Nasir Ali Khan (EtnoAntropoZum, 2016)
Among Rajputs wedding ceremony has its own procedures and events which are carried out through rituals. These rituals carry the symbolic meanings and symbolic representations for the people who practice and endorse them. This article ethnographically investigates the wedding ceremony along with the rituals performed among the Rajput people living in a small town in central Punjab (Pakistan). The research is qualitative study with participant observation and in-depth interviews as the main tools for collecting data. The study reveals that certain rituals performed during the wedding days perform two major functions. Besides providing the amusement and festivity, they produce, reproduce and reinforce stereotypical roles of women within the community. Secondly, they help bride and groom to go through a transformation of their status by assigning their new roles and expectations as husband and wife.